Co-circulation of Influenza A and B During the 2016–2017 Influenza Season at Rush University Medical Center. (4th October 2017) - Simms, Andrew; Gonzalez, Hemil; Moore, Nicholas M; Chapman, Leslie A; Lolans, Karen; Trenholme, Gordon M
Abstract: Background: Two strains of influenza B virus, B/Yamagata and B/Victoria, co-circulate in the USA, typically appearing in late March. This year, influenza B virus (FluB) co-circulated consistently with influenza A virus (FluA). We hypothesized that this could be explained by an increased use of influenza trivalent vaccine, which lacks the B/Yamagata strain, over the quadrivalent vaccine. Methods: We performed a retrospective, observational cohort study of patients with laboratory-diagnosed influenza from October 2016 through April 2017. Age, comorbidity categories, pregnancy status, symptoms, The presence of opacity on chest film, ICU admission, death, and receipt of oseltamivir were reviewed for 256 patients. A subset of FluB specimens were subtyped for lineage using RT–PCR. Results: Influenza was detected in 495 (10.4%) of 4, 754 samples collected, including 305 FluA and 190 FluB. The H3 strain represented 97% of FluA cases. FluB subtypes were: 70, B/Victoria; 21, B/Yamagata; and 41, not subtyped. Chart review was conducted for 124 randomly selected FluA and 132 sequential FluB patients. Median age of patients with FluA was 44 compared with 27 with FluB ( P < 0.001). Forty-three (34.7%) FluA patients had heart disease compared with 21 (15.9%) FluB patients ( P < 0.001). Otherwise, there were no differences in comorbidities, pregnancy status, clinical symptoms, or infectious complications between FluA vs. FluB patients. Ninety-three (75%) FluA patients and 78 (59.1%) FluB patients received oseltamivir. ICU admission occurred in 15 (12.1%) FluA and 9 (6.8%) FluB patients (OR 1.414; 95% CI 0.83-2.4). Seventy-seven (30%) patients received flu vaccine, 39 with FluA, and 38 with FluB; 97 (37.9%) were not vaccinated and 82 (32%) were missing data. Of those vaccinated, 6 patients received trivalent vaccine, and 71 received quadrivalent. Only 24 patients with B/Victoria and 7 patients with B/Yamagata were vaccinated. Conclusion: The proportion of infected patients who had received vaccination was low, limiting our ability to detect the effect of the trivalent vaccine on the incidence of infection with B/Yamagata. In contrast to conventional thought, when compared with influenza B, influenza A (predominantly H3N2) did not appear to disproportionally affect those with most medical comorbidities, and was not disproportionately associated with our identified clinical complications. Disclosures: All authors: No reported disclosures.